Work Engagement in Indonesian Small and Medium Enterprises: A Bibliometric Analysis of Emerging Research Trends - Putra, Alfa Santoso Budiwidjojo (Bulletin of Counseling and Psychotherapy, 2024)
This study aims to analyze the development of research on work engagement in Small and Medium Enterprises (SMEs) from 2020 to 2024 using a bibliometric approach. The method used is bibliometric analysis with the help of VOSviewer software for data visualization. Data was collected from the Dimensions database using the keywords "work engagement", "SMEs", and "Indonesia". The results show a significant increase in the number of publications and citations related to work engagement in SMEs during this period. Four main research clusters were identified: collaboration and communication, employee creativity and self-efficacy, innovative work behavior, and affective commitment and job satisfaction. Research trends have shifted from the basic concept of work engagement to its practical application in the context of digital transformation, innovation, and SME business sustainability. The COVID-19 pandemic has become a catalyst for research exploring the role of work engagement in SME resilience and adaptation. The need for further research integrating work engagement with contemporary issues such as digitalization and SME business resilience was revealed. The novelty of this research lies in the comprehensive analysis of work engagement research trends in Indonesian SMEs using a bibliometric approach, which has not been widely done before. This study provides a holistic mapping of the development of work engagement studies in SMEs and identifies future research directions.